Comparing para-rowing set-ups on an ergometer using kinematic movement patterns of able-bodied rowers. Issue 8 (18th April 2017) - Cutler, B.; Eger, T.; Merritt, T.; Godwin, A.
ABSTRACT: While numerous studies have investigated the biomechanics of able-bodied rowing, few studies have been completed with para-rowing set-ups. The purpose of this research was to provide benchmark data for handle kinetics and joint kinematics for able-bodied athletes rowing in para- rowing set-ups on an indoor ergometer. Able-bodied varsity rowers performed maximal trials in three para-rowing set-ups; Legs, Trunk and Arms (LTA), Trunk and Arms (TA) and Arms and Shoulders (AS) rowing. The handle force kinetics of the LTA stroke were comparable to the values for able-bodied literature. Lumbar flexion at the catch, extension at the finish and total range of motion were, however, greater than values in the literature for able-bodied athletes in the LTA set-up. Additionally, rowers in TA and AS set-ups utilised more extreme ranges of motion for lumbar flexion, elbow flexion and shoulder abduction than the LTA set-up. This study provides the first biomechanical values of the para-rowing strokes for researchers, coaches and athletes to use while promoting the safest training programmes possible for para-rowing.